Molecular Studies of Alphavirus Immunogenicity. - Strauss, James H. (1991)
Ockelbo virus, first isolated in 1982 in Sweden, causes arthritis, fever and rash in man. We have obtained the complete nucleotide sequence of Ockelbo virus and compared this sequence to that of other strains of Sindbis virus. Partial sequence analysis of five other strains of Sindbis virus was also performed. Three principal conclusions arise from our data. (1) Ockelbo is virtually identical to the causitive agents of Karelian Fever of Russian and of Pogosta disease of Finland. (2) These agents are closely related to South African strains of Sindbis virus, and Ockelbo was probably introduced into northern Sweden from Africa in the 1960's, followed by spread to Russian and Finland. (3) There exist an European-African group of closely related Sindbis viruses and an Asian-Australian group of Sindbis viruses. The alphaviruses are a widespread group of human pathogens that are endemic and epidemic in many parts of the world. They are mosquito-borne and are particularly prevalent in tropical and subtropical areas of the world, but alphaviruses pathogenic for man are also present in temperature and even Arctic areas. Many alphaviruses are capable of causing fever, rash and arthralgia in man that in some cases can be disabling for extended periods of time. Many of the New World alphaviruses can cause encephalitis in man. We wish to determine the relationships of alphaviruses and strains of alphaviruses to one another and to search for emerging viruses.